Sakrálne funkcie ženy v archaických spoločenstvách = Sacral functions of women in Archaic societies - Komorovský, Ján (Religio, 1997)
The author takes as his starting point the myth of Amazons which expresses the binarity of relations between men and women, stressing the superiority of the feminine principle in religions and cultures of the archaic world. Womanhood is closely linked to mysterious powers. Woman's physiological functions were perceived by the early man as effects of her magic power. This power, together with her psychical traits, has rendered woman especially fit for religious service. It is here that the roots of the sculptures of naked women are to be looked for. They were linked to the agrarian cult of the fertility of soil. Women could step by step take over some of the priestly functions relevant for the cult of the domestic hearth. Archaeological excavations have brought women's figures to light that were often discovered close to the fireplaces of prehistoric dwellings. Some of the Paleoasiatic peoples (Chukchi, Koryaks) have traditionally entrusted the whole family cult and all family ritual to women. The priestly functions of fire keepers and executors of rituals linked with fire have been unquestionably preserved among the Tungus (Evenks) people in Siberia. An analogous function is fulfilled by Herrero chief's first wife or her daughter as the keeper of the sacred fire of the kraal. The same typological line leads to ancient Greek Hestia or Roman Vesta. The idea of the family hearth and its keepers is an archetype present in the history of mankind since the earliest times so that the family hearth becomes a symbol the content of which is woman, wife, mother.